PENGARUH KEPEMIMPINAN, IKLIM KERJA DAN BEBAN KERJA TERHADAP KINERJA GURU PADA SMP NEGERI 3 DUMAI - Astuti, Putri Yuni; Indarti, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of leadership, work climate and workload on teacher performance, either simultaneously or partially and which variables are the most powerful influence on teacher performance. The method used in this research is descriptive statistical analysis and multiple linear regression analysis. The Samples was the entire population of teachers of SMP Negeri 3 Dumai totaling 60 people. The results of simultaneous regressions test (Test-F) showed that the independent variables have a significant effect on the dependent variable. Partial regression test (Test-t) showed that the work climate variables have the most significant effect on the variable performance of teachers. The magnitude of the effect that (R2) variable leadership, work climate and workload together on the variable performance of teachers is 58,8%, while the remaining 41,2% is influenced by other variables that are not observed in this study.The results of research and discussion concluded that leadership, work climate and workload simultaneously positive and significant impact on teacher performance. Similarly, leadership, work climate and workload partially positive and significant impact on teacher performance. The variables that most strongly to the performance of the teacher is variable work climate.Keywords : Leadership, Work Climate, Workload and Teacher Performance